"Water‐Salt‐in‐Deep Eutectic Solvent" Method to Optimize Conductivity, Viscosity and Freeze Resistance for Eutectic Electrolytes. Issue 12 (22nd September 2022) - Zhang, Yan; Wang, Yafei; Zhang, Yangming; Zhao, Jingxin; Liu, Yiyang; Guan, Ying; Zhang, Yongjun
Abstract: A novel and simple "water‐salt‐in‐deep eutectic solvent" (WS‐DES) strategy is reported here to increase the ionic conductivity, while reducing the viscosity and freezing temperature of deep eutectic solvent (DES). Upon the addition of water and strong electrolyte salt to the DES of [LiTFSI][EG], the conductivity was increased by 16 times, the viscosity was decreased by 36 %, and the freezing temperature was decreased by 30 °C. Additionally, WS‐DES strategy can be well applied to electrolytes for supercapacitor devices. Compared to the initial DES, supercapacitors using WS‐DES electrolyte have higher specific capacitance, better rate performance, lower IR voltage drop, and lower internal resistance. Moreover, the WS‐DES electrolyte also exhibits excellent electrochemical stability under extreme condition even at −40 °C. Abstract : Better electrolyte : A facile "water‐salt‐in‐deep eutectic solvent" strategy is reported here to increase the ionic conductivity, while reducing the viscosity and freezing temperature for eutectic electrolytes. Compared to the initial DES, supercapacitors using "water‐salt‐in‐deep eutectic solvent" electrolyte have higher specific capacitance, better rate performance, lower IR voltage drop, and lower internal resistance.